2021
DOI: 10.3390/en14175583
|View full text |Cite
|
Sign up to set email alerts
|

Influence of LPG and DME Composition on Spark Ignition Engine Performance

Abstract: This article presents a detailed analysis of the potential of dimethyl ether (DME) fuel applications in SI engines. This paper presents the tests results completed on an 1.6-dm3 Opel Astra engine fueled by gaseous fuel as a mixture of LPG and DME. Dimethyl ether is a fuel with properties similar to liquid LPG fuel. In addition, DME is very well miscible with LPG, hence the possibility of creating a mixture with any DME divisions. The assessment of the possibility of using DME as a component of the mixture was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The results of the studies presented in three papers validate the alternative fuel additives [1,4,5]. Fabiś et al [1] present the potential of dimethyl ether as fuel for SI engines.…”
Section: Contributions In This Issuementioning
confidence: 65%
See 2 more Smart Citations
“…The results of the studies presented in three papers validate the alternative fuel additives [1,4,5]. Fabiś et al [1] present the potential of dimethyl ether as fuel for SI engines.…”
Section: Contributions In This Issuementioning
confidence: 65%
“…The results of the studies presented in three papers validate the alternative fuel additives [1,4,5]. Fabiś et al [1] present the potential of dimethyl ether as fuel for SI engines. Paneerselvam et al [4] evaluate peppermint bio-oil as an additive applied as a cetane improver.…”
Section: Contributions In This Issuementioning
confidence: 65%
See 1 more Smart Citation
“…Various injection strategies [3][4][5][6][7][8], engine operation conditions [9][10][11] and fuel blends [12][13][14][15][16][17][18] of DME-fueled engines have been investigated. Youn et al [8] showed that the use of DME was associated with a higher pressure and earlier increase in the Energies 2022, 15,1912 2 of 11 heat release rate (HRR) compared to diesel, because the ignition delay was shorter, the vaporization characteristics were more favorable, and the cetane number was higher.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of indicator diagrams is described comprehensively in the literature. On their basis, the influence of fuel used [ 15 , 16 , 17 ], ignition timing [ 18 ], valve opening and closing [ 19 ], or the technical condition [ 12 , 20 , 21 ] on the combustion process are determined. On the basis of pressure in the combustion chamber, the loads on the mechanical components of an engine are determined.…”
Section: Introductionmentioning
confidence: 99%